An Efficient Algorithm Image Processing Technique Using Bilateral Filtering Method: A Novel Approach for High-Density Noise Removal in Images Using Bilateral Filtering (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The majority of the image preparing techniques, for example, edge location, division, objects following, design acknowledgment and so forth don't perform well in the event of noise. Subsequently, image rebuilding as a preprocessing step is performed before applying the image to any of the past referenced techniques. This suggests a new and effective algorithm for the expulsion of high-density salt and pepper noise in photographs and videos. Current non-direct filters such as Standard Median Filter (SMF), Adaptive Median Filter (AMF), Decision Based Algorithm (DBA), and Robust Estimating Algorithm (REA) show better efficiency at low and medium noise densities. At high noise densities, their exhibition is poor. A new algorithm to expel high-density salt and pepper noise utilizing changed sheer arranging technique is proposed. The new algorithm has lower calculation time when contrasted with other standard algorithms. The demonstration of the framework is investigated as far as Mean square blunder (MSE), Peak sign to noise proportion (PSNR) image improvement factor (IEF) and time required for executing the algorithms for various noise densities. Reproduction results shows that proposed algorithm beats the current algorithms even at high noise densities for shading images. Numerous investigations are led to approve effectiveness of the proposed algorithm.